The Ruling Class Based on a Play by Peter Barnes - Medak, Peter; Hodges, Ken; O'Toole, Peter; Sim, Alastair; Lowe, Arthur (The Criterion Collection, 2001)
In this still savage if lengthy British satire, Peter O'Toole gives one of his most ballistic performances as Jack Arnold Alexander Tancred Gurney. Jack's just become the 14th Earl of Gurney, but he prefers to be known as God. Yes, he's bonkers, with long, golden Jesus locks to complete the package. His stuffy relatives conspire to have him put away, but not before marrying him off to his uncle's mistress so that Jack can produce an heir. Jack's psychiatrist proposes a more radical course of action: a confrontation between Jack and the Electric Messiah, who shocks the gentle young man into adopting more socially acceptable delusions ... "The Ruling Class" remains the only film to ever combine elements of Jacobean drama, Brechtian satire, Hammer horror and musical comedy. Much misunderstood, it still ranks as one of the great British films of its era, largely thanks to O'Toole's holy tomfoolery. [www.eye.net]